Effects of Cannabidiol and Hypothermia on Short-Term Brain Damage in New-Born Piglets after Acute Hypoxia-Ischemia - Lafuente, Hector; Pazos, Maria R.; Alvarez, Antonia; Mohammed, Nagat; Santos, Martín; Arizti, Maialen; Alvarez, Francisco J.; Martinez-Orgado, Jose A. (Frontiers in Neuroscience, 2016)
Background: Hypothermia is standard treatment for neonatal encephalopathy, but near 50% of treated infants have adverse outcomes. Pharmacological therapies can act through complementary mechanisms to hypothermia and would improve neuroprotection. Cannabidiol could be a good candidate. Objective: To test whether immediate treatment with cannabidiol and hypothermia act through complementary brain pathways in hypoxic-ischemic newborn piglets. Methods: Hypoxic-ischemic animals were randomized to receive 30 min after the insult: 1) normothermia- and vehicle-treated group; 2) normothermia- and cannabidiol-treated group; 3) hypothermia- and vehicle-treated group; and 4) hypothermia- and cannabidiol-treated group. Six hours after treatment, brains were processed to qualify the number of neurons by Nissl staining. Proton nuclear magnetic resonance spectra were obtained and analyzed for lactate, N-acetyl-aspartate and glutamate. Metabolite ratios were calculated to assess neuronal damage (lactate/N-acetyl-aspartate) and excitotoxicity (glutamate/Nacetyl-aspartate). Western blot studies were performed to quantify protein nitrosylation (oxidative stress) and expression of caspase-3 (apoptosis) and TNFα (inflammation). Results: Individually, the hypothermia and the cannabidiol treatments reduced the glutamate/Nacetyl-aspartate ratio, as well as TNFα and oxidized protein levels. Also, both therapies reduced the number of necrotic neurons and prevented an increase in lactate/N-acetyl-aspartate ratio. The combined effect of hypothermia and cannabidiol on excitotoxicity, inflammation and oxidative stress, and on histological damage, was greater than either hypothermia or cannabidiol alone. Conclusion: Cannabidiol and hypothermia act complementarily and show additive effects on the main factors leading to hypoxic-ischemic brain damage.